Study of Landslide Susceptibility on Geotechnic and Soil Hydrological Characteristics - Marchel Maxy Rijoly; Pieter Jozef Kunu; Rafael Martinus Osok (Jurnal Agroekoteknologi, 2026)
This study aims to analyze the physical, geotechnical, hydrological, and mineralogical properties of soil, as well as the presence of slip surfaces and their influence on the landslide potential of "dusung" land resulting from rock mining activities on the slopes of hills within the Wai Sikula watershed, Ambon Island. The research was conducted at rock mining sites in the Wai Sikula watershed, Negeri Hatu, Leihitu Barat District, Central Maluku Regency, from February to April 2026. The methods employed in this study include field surveys and observations at landslide points, along with laboratory analysis of soil samples. The results indicate that the soil characteristics influencing "dusung" land landslides due to rock mining include high bulk density (1.73 g/cm³), high particle density (2.57 g/cm³), high soil porosity (63.62%), rapid infiltration rate, low plastic limit (37.98%), low internal friction angle (17°), low shear strength indicating high landslide vulnerability (0.018 kg/cm²), and low cohesion (-0.005 kg/cm²), all of which increase the risk of landslides. The study area is composed of volcanic breccia and tuffaceous sandstone with steep slope conditions. Weak geotechnical and hydrological soil characteristics contribute significantly to the occurrence of "dusung" land landslides in the rock mining areas of the Wai Sikula watershed, Ambon Island. Keywords: Agroforestry, geotechnical, hydrological, landslides, physical properties